النظرية السيميائية السردية وتجلياتها في التجربة النقدية للسعيد بنكراد - قمولي, فاطمة; شيخة, محمد الامين (جامعة الوادي - University of Eloued, 2023)
تعدّ تجربة الناقد المغربي السعيد بنكراد واحدة من بين أهم التجارب المتميزة والمتفردة في النقد العربي عامة والمغاربي خاصة، إذ يتحكم فيها وعي نقدي وثقافي يحاول تكييف المناهج النقدية الغربية وطبيعة النص المعالج، والمطلع على أعمال الناقد يدرك أصالة هذه التجربة وتنوع مصادرها وآلياتها، هذا التنوع المنهجي كان له انعكاس واضح على طريقة مساءلة النصوص وفق المنهجي السيميائي المنفتح على الأبعاد الأيديولوجية والتأويلية، ومن هنا جاءت هذه الدراسة للكشف عن معالم النقد السيميائي في تجربة السعيد بنكراد تنظيرا وتطبيقا، وتتبع التطور المنهجي في هذه التجربة من خلال بعض من مؤلفاته، كما تسعى لإبراز الآليات التي اعتمدها في قراءاته السيميائية لمختلف أشكال النصوص السردية، مع الحرص على بيان خصوصيات تلقيه وتطبيقه للمنهج السيميائي . Abstract: Saeed Benkrad, a Moroccan critic, espouses a distinctive and singular perspective in Arab criticism, particularly within Moroccan context. His critical and cultural consciousness adapts Western critical methodologies to suit the specific nature of the text under examination. Those familiar with Benkrad's works appreciate the authenticity and diversity of his sources and mechanisms. This methodological diversity manifests in his semiotic framework, which scrutinizes texts with a receptive and perceptive approach to ideological and interpretive dimensions. The primary aim of this study is to uncover the semiotic features of Benkrad's critical perspective, both theoretically and practically, while charting the methodological evolution of his approach through selected works. Moreover, this study seeks to accentuate the mechanisms utilized in his semiotic readings of various narrative texts, while highlighting the unique attributes of his reception and implementation of semiotic methodology.
Article
Keywords: النظرية السيميائية - السرد – النقد –القراءة - التأويل – السعيد بنكراد